Railway Concessions : Heading Down the Right Track in Argentina - Carbajo, José; Estache, Antonio (World Bank, Washington, DC, 2012)
Argentina privatized many of its railway services by concession contract during the early 1990s. The reforms have been remarkable for their speed and innovation - despite the complexity of the issues and the lack of "off-the-shelf" models to follow at the time. The overall result has been positive. Many services have improved. Traffic has grown-up about 180 million passenger trips a year. Subsidies have been cut dramatically - down from US$2 billion or so a year to a little more that US$100 million. But as with any complex reform, there is an unfinished agenda. And with the Argentine approach becoming a model for other countries in Latin America this review of the lessons starting to emerge from the reform experience is a timely one.